2012
DOI: 10.1007/s10648-012-9205-z
|View full text |Cite
|
Sign up to set email alerts
|

Using Spacing to Enhance Diverse Forms of Learning: Review of Recent Research and Implications for Instruction

Abstract: Every day students and instructors are faced with the decision of when to study information. The timing of study, and how it affects memory retention, has been explored for many years in research on human learning. This research has shown that performance on final tests of learning is improved if multiple study sessions are separated-i.e., "spaced" apart-in time rather than massed in immediate succession. In this article, we review research findings of the types of learning that benefit from spaced study, demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
226
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(259 citation statements)
references
References 46 publications
(56 reference statements)
10
226
1
6
Order By: Relevance
“…It is possible that these effects may differ across a longer retention interval. The length of the retention interval has sometimes affected other memory phenomena, such as the testing effect (e.g., Coppens, Verkoeijen, & Rikers, 2011;Roediger & Karpicke, 2006a;Toppino & Cohen, 2009) and the spacing effect (e.g., Carpenter, Cepeda, Rohrer, Kang, & Pashler, 2012;Cepeda, Vul, Rohrer, Wixted, & Pashler, 2008;Rohrer & Taylor, 2006), such that these manipulations sometimes produce stronger effects after longer, as opposed to shorter, retention intervals. Previous studies on interleaving have shown significant benefits of interleaving after relatively short retention intervals of several seconds (e.g., Kornell & Bjork, 2008;Wahlheim et al, 2011) or minutes (e.g., , suggesting that reliable effects of interleaving can occur even when memory is assessed relatively soon after learning.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these effects may differ across a longer retention interval. The length of the retention interval has sometimes affected other memory phenomena, such as the testing effect (e.g., Coppens, Verkoeijen, & Rikers, 2011;Roediger & Karpicke, 2006a;Toppino & Cohen, 2009) and the spacing effect (e.g., Carpenter, Cepeda, Rohrer, Kang, & Pashler, 2012;Cepeda, Vul, Rohrer, Wixted, & Pashler, 2008;Rohrer & Taylor, 2006), such that these manipulations sometimes produce stronger effects after longer, as opposed to shorter, retention intervals. Previous studies on interleaving have shown significant benefits of interleaving after relatively short retention intervals of several seconds (e.g., Kornell & Bjork, 2008;Wahlheim et al, 2011) or minutes (e.g., , suggesting that reliable effects of interleaving can occur even when memory is assessed relatively soon after learning.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the evidence shows that people forget rapidly, especially during the initial period after learning (Carpenter et al, 2012). Forgetting curves document the relationship between the percent of correct information recalled and the time elapsed since the information was learned.…”
Section: Learning About Learningmentioning
confidence: 99%
“…As early as 1885 Ebbinghaus determined that it is better to use a distributed approach with several short iterations for recalling memories, rather than trying to achieve the same result in just one long session [33]. This approach, to leave time between learning sessions, is called spacing and has proven to be more effective in comparison to a massed approach where no time is left in between learning sessions [12], [13]. This effect is especially useful in education where it can lead to better memory retention without having to invest more learning time [34].…”
Section: Spaced Learningmentioning
confidence: 99%
“…We are trying to get students to learn more frequently instead of having them try to mass their entire learning material into a couple of days before an exam. It is our aspiration that students will change their learning habit by adapting the successfully proven spaced learning approach [12], [13] which will then hopefully have a positive effect on their overall academic performance. The use of gamification will motivate participants to use our artifact, and push notification will constantly try to influence their behavior to stick to a given schedule.…”
Section: Introductionmentioning
confidence: 99%